Pain sensitivity in general practice - Smith, Robert (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 1957)
This investigation was carried out during the ordinary routine work of general practice. It consisted of applying a simple test and considering the result in relation to the general clinical picture. The test is performed with an instrument known as a Pressure Algometer. The principle of this test and the technique of its application was fully described by Dr. K.D. Keele, M.D., F.R.C.P., Ashford Hospital, Middlesex, in the Lancet in 1954. The writer owes much to him for advice and encouragement in introducing this test into routine general practice. The thesis is divided into three main parts. The first part deals with the problem of pain and pain sensitivity, methods of estimating pain sensitivity including pressure algometry, a description of the instrument and the technique for its use in general practice. The second part consists of tabulated results and their analysis. Finally details are given of cases chosen from different sensitivity groups, from which it may be seen that the information provided by the test fits into the general clinical picture and on occasions is of value in management and diagnosis.
Keywords: Medicine, M.D.; M.D. Trinity College Dublin